Association between serum ferritin level and bone mineral density in adult females of Dhaka city - Rahman, Nishat; Akhter, Qazi S.; Busra, Khadijatul; Saha, Manasi; Islam, Nawshin; Akter, Mahbuba; Sarker, Keya; Rahman, Mostafizur (International Journal of Research in Medical Sciences, 2025)
Background: Osteoporosis and osteopenia are among the alarming issues worldwide affecting people of all ages. Bone mass is influenced by several factors including iron. Iron deficiency is common in Bangladesh among the women of reproductive age group. So, iron depletion could have a detrimental impact on bone, resulting in episodes of fracture. The present study was carried out to assess the association of serum ferritin level and bone mineral density in adult females. Methods: A cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2018 to June 2019. A total of 122 adult females of age ranging from 18-44 years were enrolled. Eligible subjects were divided into three groups on the basis of hemoglobin concentration. The serum ferritin level and bone mineral density were measured. For statistical analysis, One-way ANOVA followed by Bonferroni test and Pearson’s correlation coefficient (r) were performed as applicable using SPSS for windows version 25.0. Results: The mean (±SD) serum ferritin level and BMD T score of lumbar spine and femoral neck showed significant differences among the groups (p<0.001, p=0.002, p=0.001 respectively). We found positive correlation (r±0.378 and r±0.353 respectively) between serum ferritin level and BMD T score of both lumbar spine and femoral neck which was statistically significant (p<0.001). Conclusions: Low serum ferritin level is positively associated with low bone mineral density among adult females of Dhaka city. Therefore, early detection and correction of iron deficiency could be an important preventive measure against the disruption of bone composition at various stages of life.